2014
DOI: 10.2105/ajph.2013.301383
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation and Suicide Ideation, Plans, Attempts, and Medically Serious Attempts: Evidence From Local Youth Risk Behavior Surveys, 2001–2009

Abstract: Regardless of sexual orientation measure used, most SMY subgroups had increased odds of all SROs. However, many factors are associated with SROs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
79
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 58 publications
9
79
1
2
Order By: Relevance
“…In adjusted analyses, males with same- or both-sex intercourse experiences were higher in SROs compared with males who had only experienced opposite-sex intercourse. Many studies have reported higher rates of SROs among gay males when compared to lesbian females [3, 18, 19]. Based on our study, we were able to confirm that violence is a risk factor for suicide among youths with same- or both-sex intercourse.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In adjusted analyses, males with same- or both-sex intercourse experiences were higher in SROs compared with males who had only experienced opposite-sex intercourse. Many studies have reported higher rates of SROs among gay males when compared to lesbian females [3, 18, 19]. Based on our study, we were able to confirm that violence is a risk factor for suicide among youths with same- or both-sex intercourse.…”
Section: Discussionsupporting
confidence: 74%
“…Variables that influence the suicidal behavior were depression and ever having had sexual intercourse as youths [2]. Media reports convey the message that lesbian, gay, or bisexual (LGB) youths have much greater rates of suicide than non-LGB youths [3]. LGB youths experience stress and depression during the formation of their sexual identity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2---5 Regardless of whether youths self-identify as LGB or report same-sex attraction or sexual contact, LGB youths have higher odds of reporting suicidal thoughts, plans, and attempts. 2,4,5 The strain of coping with the stigma of being a sexual minority in a society in which heterosexuality is normative is often referenced for explaining why LGB youths are at higher risk for suicide. 4,6 In fact, studies show that when youths attend schools with cultures that are more likely to stigmatize LGB youths, their mental health outcomes are even worse.…”
mentioning
confidence: 99%
“…2,3 The minority stress theory suggests that minority groups are disadvantaged in a number of ways, and certain stressors that do not have an impact on advantaged groups are burdensome to disadvantaged groups. 4 Research shows that LGB adolescents are more likely to use substances, 3,517 report suicide ideation, attempt suicide, 57,12,13,1829 and be exposed to vio-lence and victimization 3,5,6,12,26,3033 than are heterosexual adolescents.…”
mentioning
confidence: 99%